MEDIA INFLUENCE ON POLITICAL PARTIES IN ALBANIA - Xhaferaj, Anjeza (Advances in Social Sciences Research Journal, 2015)
This article investigates the role of television on the structure and organization of political parties in the post – communist Albania. The existing literature on political parties links the structure of mass parties with the written press, and the structure of electoral- professional and cartel parties with the increasing influence of television. The mass party is based on the principle of membership. Among many tasks that members had to carry out, the dissemination of party’s declarations, statements, opinions and ideology, through the distribution of party press is one of the most important. The studies on political parties have observed the emergence of the catch-all, electoral-professional and cartel party, in which the party leaders have substituted the membership organizational network with television, and thus minimized the role of intermediate party organs. In difference from their counterparts in Western Europe, in the new established democracies of post-communist countries, political parties were born in a period characterized by a modern and developed media which was accessible to everyone. Therefore, the immediate access to modern means of communication has distanced the parties from the society since the early phases of their inceptions, without giving them the opportunity and necessity to organize territorially. This article analysed the techniques that have used the Albanian political parties to communicate with their electorate, concluding that in the moment of their creation, television could not serve to the opposition parties as a means of information. That is why they had to rely heavily on the written press and their membership. The opening of some broadcasting channels, after 2000, made possible the access on modern techniques of communication, leading to a minor role of the press and membership. As a result we could say that at the early phase of democratic process, the political parties in Albania shared features of the mass party with a strong territorial penetration, features that started to fade out when television gained a more prominent role in the organization of electoral campaigns by influencing thus a more contemporary western alike model of party organization.